Association between dosing of spironolactone and outcomes in heart failure with preserved ejection fraction patients combined with chronic kidney disease------Balance of efficacy and risk - Li, Jun-Feng; Qu, Xiang; Gao, Zhan; Chen, Chang-Xi; Zhang, Feng-Yu; Cheng, Ling; Zhou, Xi; Zhou, Hao (Frontiers in Pharmacology, 2023)
Aims: Few studies have compared the association between dosing of spironolactone and outcomes in patients with heart failure with preserved ejection fraction (HFpEF), and whether spironolactone dose could significantly affect the prognosis of HFpEF patients combined with chronic kidney disease (CKD) remains unclear. Our aim was to directly compare ‘high vs. low’ doses of spironolactone in an attempt to find a benefit-risk-balanced point, and infer an adequate dose for HFpEF with CKD patients. Methods: Overall, 4321 symptomatic heart failure inpatients were initially screened from January 2013 to December 2019, and all enrolled patients were followed-up for 36 months; After including patients who meet the diagnostic criteria of HFpEF and CKD with ejection fraction >45% and estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m2, a total of 387 patients was selected. Primary outcome was a composite of all-cause death, heart failure (HF) hospitalization and non-fatal stroke. The key safety outcome was hyperkalemia rates during the follow-up period. Results: The primary outcome event rates in patients with or without spironolactone were 12.74 and 21.45 per 100 person-years, respectively. Compared with patients not taking spironolactone, the adjusted hazard ratio (HR) (95% confidence interval [CI]) was 0.55 (0.38-0.79) with spironolactone group for primary outcomes. After grouped by the daily dose of spironolactone, low-dose group (≤40 mg) was associated with lower relative risk for the primary efficacy outcome (adjusted HR (95% CI) was 0.43 (0.23–0.81), 0.50 (0.33–0.76) and 0.74 (0.36–2.79) with <40mg, 40mg and >40mg, respectively). During 3-year follow-up, the risk for hyperkalemia was amplified in the higher dose group (>40mg) while showed no significant difference compared with low dose group (P=0.425). Conclusions: HFpEF with CKD patients using spironolactone had lower risk of adverse cardiovascular outcomes. And the use of low-dose spironolactone (≤40 mg) showed the best efficacy and safety, therefore we may recommend ≤40mg as the optimal initial dose for these patients. However, this was a relatively small sample size, retrospective study, and further adequately powered randomized trials are needed to verify these results.